Histología y lipoperoxidación renal en ratas ejercitadas sobre una caminadora y sometidas a restricción de agua - Lorençoni, Roselene Modolo Regueiro; Pelai, Elisa Bizetti; Godoy, Moacir Fernandes; Dos Santos, Alice Cristina Antonio; Miyoshi, Lívia Hissae; De Oliveira, Rebeca Nicolás Paronetto; Padovani, Carlos Roberto; Fregonesi, Cristina Elena Prado Teles; Camargo Filho, José Carlos Silva (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2015)
Physical effort stimulates an increase in oxygen consumption in tissues, generating toxic chemical species derived from oxygen (ROS), which are considered the initiators of the lipid peroxidation process (LPO), the major mechanism of cellular injury. As the essential mechanism for maintaining the electrolyte balance depends on an effective kidney function, oxidative stress in this organ can be a key factor in the development and persistence of hypertension. This study aimed to determine the kidney changes induced by a combination of fluid restriction and exercise in rats. The study consisted of 24 male Wistar rats of 90 days of age, divided into four groups, two of which were submitted to water restriction and exercise on a treadmill. Twenty-four hours after the last training session, the animals were euthanized and the left kidney was removed. The upper part of the kidney was used for the histological procedures and the lower part for the quantification of membrane lipoperoxides. Analysis of variance was applied after testing the normality of data, and the comparison between groups was performed using the Bonferroni test, adopting a significance of p<0.05. The restriction had an influence on body weight; kidney weight; proximal tubule maximum diameter; and area, perimeter and diameter of glomeruli, whereas the exercise affected the weight and the minimum diameter of the proximal tubule. According to the TBARS (thiobarbituric acid reactive substances) method, there was a difference between the G1 (control) and G3 (sedentary with water restriction) and between the G2 (exercised with water) and G4 (exercised with water restriction) compared to G1. The treadmill exercise combined with the water restriction promoted structural changes in the glomeruli and promoted oxidative stress, although neither variable corroborated for the potentiating of lipid peroxidation.
Histology and renal lipoperoxidation in rats exercised on a treadmill and submitted to water restriction
Keywords: Kidney; Morphology; Oxidative stress